2022
DOI: 10.21203/rs.3.rs-1806260/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A strong association between the VDR gene markers and SARS-CoV-2 variants

Abstract: IntroductionA COVID-19 disease, caused by the SARS-CoV-2, created significant concern since December 2019 worldwide. The virus is known to be highly transmissible. Heterogenic clinical features even vary more among SARS-CoV-2 variants from asymptomatic forms to severe symptoms. Previous studies revealed an association between COVID-19 and vitamin D deficiency resulting from its low levels in COVID-19 patients. To our knowledge, there is no scientific investigation that evaluates the direct association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…A number of observational studies have evaluated the association between vitamin D-related polymorphisms and risk of COVID-19 infection and severity [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116]. As shown in Table 1, most studies are from European and Middle eastern countries and included a relatively small number of participants.…”
Section: Genetic Variations Of Vitamin D Pathway and Covid-19 Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of observational studies have evaluated the association between vitamin D-related polymorphisms and risk of COVID-19 infection and severity [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116]. As shown in Table 1, most studies are from European and Middle eastern countries and included a relatively small number of participants.…”
Section: Genetic Variations Of Vitamin D Pathway and Covid-19 Infectionmentioning
confidence: 99%
“…Six retrospective cohort studies from Turkey, Iran, Portugal, United Arab Emirates, Serbia, and Cuba investigated the association between vitamin D-related polymorphisms and COVID-19 severity [102][103][104][105][106][107]. Four case-control studies from Italy, Iran, and Cyprus reported the association between VDR polymorphism and COVID-19 susceptibility [108][109][110][111], while one study from Iran reported the association between VDR polymorphism and COVID-19 mortality [112].…”
Section: Genetic Variations Of Vitamin D Pathway and Covid-19 Infectionmentioning
confidence: 99%
See 1 more Smart Citation